2008
DOI: 10.1111/j.1537-2995.2008.01735.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cryopreservation on red blood cell microvesiculation, phosphatidylserine externalization, and CD47 expression

Abstract: High-glycerol cryopreservation does not induce microvesiculation, PS exposure, and loss of CD47 expression in RBC membranes. Since prolonged prefreeze storage can result in RBC membrane injury during the postdeglycerolization storage period, more defined criteria for this variable should be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 45 publications
8
33
0
3
Order By: Relevance
“…On the other hand, alterations in electrolyte levels were thought to have resulted from the rinsing series during deglycerolization process since intracellular K + flows out whereas extracellular Na + flows in through the cellular membrane during freezing and storage processes of RBCs, which eventually serves the electrolyte balance mechanisms (Hogman and Meryman 1999). The results of Holovati et al (2008), who pointed out the depletion of potassium during deglycerolization was compatible with our findings. It was a remarkable finding that Sup.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, alterations in electrolyte levels were thought to have resulted from the rinsing series during deglycerolization process since intracellular K + flows out whereas extracellular Na + flows in through the cellular membrane during freezing and storage processes of RBCs, which eventually serves the electrolyte balance mechanisms (Hogman and Meryman 1999). The results of Holovati et al (2008), who pointed out the depletion of potassium during deglycerolization was compatible with our findings. It was a remarkable finding that Sup.…”
Section: Discussionsupporting
confidence: 92%
“…Since all metabolic and biochemical activities are suppressed within the cell during the freezing process (Holovati et al 2008), a decrease in ATP concentration is not to be expected. However, thawing haemolysis (Kim et al 2004) may cause a decrease in ATP levels, which is closely associated with that of 2,3-DPG (Hess and Greenwalt 2002;Holme 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was also suggested that alterations in stored erythrocytes result not only from intracellular factors and storage conditions but also from contaminating leukocytes and their side products (Andreu 1991;Holovati et al 2008). Therefore, the necessity of a closed system processing unit ensuring stringent control against bacterial contamination was particularly underlined (Battaglia 2000;Lucas et al 2004).…”
mentioning
confidence: 99%
“…Важливо відзначити, що в суспензіях розморожених еритроцитів постійно спостерігаються тран-сформовані клітини. Відомо, що везикуляція мембран еритроцитів може відбуватися як в стресових [18], так і в фізіологічних умовах, зокрема, в процесі старіння in vivo [19]. Та-ким чином клітини позбавляються від діля-нок мембрани, які несуть в собі специфічні ознаки старіння і можуть розпізнаватися іму-нокомпетентними клітинами, що дає змогу їм безпечно залишатися довгий час у руслі крові [19].…”
Section: схема дослідуunclassified
“…При гіпотермічному зберіганні еритроци-тів зміни структури плазматичної мембрани пов'язані з метаболічними порушеннями і окисними процесами, які торкаються ліпід-них і білкових компонентів мембрани [18]. Оскільки зберігання еритроцитів за умов гіпотермії до 10 діб несуттєво впливало на характеристики CD44, можна зробити ви-сновок, що цей період часу не є критичним для розвитку пошкоджень мембрани, які б позначалися на стабільності клітин, зокрема, не було виявлено сублетальних ушкоджень, пов'язаних з змінами характеристик CD44.…”
Section: схема дослідуunclassified